Relationship of Vertical Jump Test with Anthropometric Parameters and Body Composition in University Students- A Gender Variation - Amit Bandyopadhyay; Rishna Dalui; Michael Kalinski; Anindita Singha Roy (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
Vertical jump test (VJT) is one of the important determinants of physical fitness. VJT score in school going children of West Bengal, India has been reported. However, pertinent data in young sedentary Indian males and females are unavailable. Moreover, the relationship of VJT with anthropometric parameters and different components of body composition has not yet been explored in Indian context. Debatable findings have been reported regarding the impact of body composition on VJT score. The present study was aimed to evaluate the VJT score in young sedentary Indian university students and its relationship with anthropometric parameters and different components of body composition with special reference to gender variation. Healthy sedentary university students (males n=40 and females n=40) with similar socio-economic background and age group of 21–25 years were randomly sampled for the study from the post-graduate section of the University of Calcutta, Kolkata, India. VJT was evaluated by Sargent Jump Test, and body composition was determined by skinfold measurements. Body height, body mass, %Fat, Total Fat (TF), LBM and VJT score depicted significant (p<0.001) difference between male and female groups. The VJT scores obtained in the male and female groups were in the range of below average and poor, respectively. Physical parameters did not influence the VJT score in both genders. In the present study the VJT score exhibited significant (p<0.001) negative correlation with %fat, individual skinfold, sum of skinfolds, and TF. Hence, body fat content posed as a hindrance to achieve higher jumping height, especially in females, where the lean mass helped to achieve greater VJT score in males.